Keraguan Kepada Tuhan pada Remaja - Muhammad Idrus (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
This article is an effort to describe the from childhood to adolescence. The Fowler’s theory of faith development is used as reference. The focus of this article is to answer the question of how children who already developed (learned from child) can later on show doubt in their religion. The failure to overcome the life crisis and social influence is believed to be the important of emergence of the religious doubts. Keywords: Religious doubt, faith development, adolescence